Imobilização de lipases por adsorção e ligação covalente em derivados de agarose e quitosana e sua aplicação em biocatálise - Quilles Junior, José Carlos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In the biocatalysis is necessary their immobilization on inert supports for further reuse, stabilization, purification and hyperactivaction of the biocatalyst. This study aimed to immobilization of different lipases using different supports (ionic, hydrophobic and covalent) and to evaluate the activity, selectivity, stability and purification of these immobilized proteins. The chapter 1 of the work describes some techniques of immobilization and pre-purification of crude lipases from Acremonium sp by ultrafiltration showed higher activity and yield of immobilization on octyl- and phenyl-agarose. The activity of these immobilized enzymes was hyperactived by incubation at 0.01 m∙L-1 NaCl and higher concentrations of this salt was observed a decrease on the enzyme activity. The hydrolytic activity of the immobilized lipase was influenced by the vegetable oil source. In Chapter 2 we present the chemical modification and characterization of chitosan previously activated with glycidol, epichlorohydrin and glutaraldehyde for subsequent use as support for immobilization of lipases, but the low surface area of chitosan determined by BET (4 cm²∙g-1) negatively affected the immobilization process. The use of ultrasound radiation in biotransesterification of soybean oil catalyzed by immobilized lipases (TLL and L435) by hydrophobic interaction was studied in Chapter 3, and the yield of total production of esters by soybean, corn and sunflower oils. The soybean and corn oils showed highest transesterification and an increased ester production of 400 % obtained was when sonicated. The last chapter of this search presents the results obtained in the Instituto de Catálisis y Petroleoquímica de Madrid during the research stage, which focused on the improvement of the methods of immobilization of lipases and applications in the enantioselective hydrolysis and production of omega-3 from fish oil, with lipase B from Candida antarctica showing ...

Na biocatálise faz-se necessária a imobilização destas enzimas em suportes inertes ao meio reacional, a fim de reutilizar, estabilizar, purificar e muitas vezes melhorar a atividade enzimática, levando à uma hiperativação. O presente trabalho teve como objetivo principal utilizar técnicas de imobilização de enzimas sob diferentes suportes (iônicos, hidrofóbicos e covalentes) e aplicá-los na imobilização de distintas lipases para avaliar o efeito da imobilização na atividade, seletividade, estabilidade e purificação dessas proteínas. O Capítulo 1 do trabalho relata algumas técnicas de imobilização e pré-purificação das lipases brutas obtidas a partir do fungo Acremonium sp, no qual as enzimas pré-purificadas por ultrafiltração apresentaram maior atividade e rendimento de imobilização sob os suportes hidrofóbicos octil- e fenil-agarose. Essas enzimas imobilizadas foram hiperativadas na presença de 0,01 mol∙L-1 de NaCl e concentrações maiores desse sal causaram a diminuição da atividade enzimática. A atividade hidrolítica das lipases imobilizadas foi avaliada utilizando diferentes fontes de óleos vegetais, com maior atividade para enzima imobilizada do que a enzima solúvel em 40% dos óleos testados. No Capítulo 2 é apresentada a modificação química e caracterização da quitosana ativada com glicidol, epicloridrina e glutaraldeído para posterior aplicação como suporte para imobilização de lipases por ligação covalente, porém tal procedimento não foi possível devido à baixa área superficial do polímero (cerca de 4cm²·g-1) tanto para reagir com os agentes modificantes quanto para o carregamento proteico. A utilização da radiação do ultrassom na biotransesterificação do óleo de soja catalisada por lipases imobilizadas (TLL e L435) por interação hidrofóbica foi estudada no Capítulo 3, bem como o rendimento de produção total de ésteres dos óleos de soja, milho e girassol ...
Keywords: Química ambiental; Enzimas imobilizadas; Lipase; Biodiesel; Acidos graxos; Quitosana; Immobilized enzymes